2016
DOI: 10.1155/2016/4157313
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Early Diabetic Nephropathy by Islet Transplantation under the Kidney Capsule in a Rat Model

Abstract: Objective. Diabetic nephropathy (DN) is a common microvascular complication of diabetes mellitus, and insulin therapy has many side effects in the treatment of DN. Islet transplantation has emerged as a promising therapy for diabetic patients. This study was established to investigate its advantageous effects in a rat model of early DN. Methods. Streptozotocin was administered to the rats to induce diabetes. Twelve weeks later, the diabetic rats were divided into 3 groups: the islet-transplanted group (IT grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…
Figure 2Meta-analysis of the studies assessing glomerular volume: A) studies with different times of exposure to diabetes (two or four weeks); B) studies with equal times of exposure to diabetes (two weeks). Mean values, standard deviations, differences between mean values, and 95% confidence interval were raised to 10 6
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…
Figure 2Meta-analysis of the studies assessing glomerular volume: A) studies with different times of exposure to diabetes (two or four weeks); B) studies with equal times of exposure to diabetes (two weeks). Mean values, standard deviations, differences between mean values, and 95% confidence interval were raised to 10 6
…”
Section: Resultsmentioning
confidence: 99%
“…, 6 Structural changes include glomerular and renal hypertrophy, thickening of the basement membrane, tubular atrophy, and interstitial fibrosis, which in turn foster the development of hyperfiltration, proteinuria, and decreased renal function 26. Screening for DKD includes annual urine albumin and glomerular filtration rate (GFR) tests 7…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recipients can obtain additional donor islet cells through repeated surgeries,to fully restore blood glucose levels in diabetic patients to normal levels [ 13 , 14 ]. Recent studies have shown that pancreas or islet transplantation can ameliorate and even reverse diabetic complications, including nephropathy, retinopathy and neuropathy in the early stage [ 15 17 ]. However, the effect of islet transplantation on DMED has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, islet transplantation can effectively prevent and reverse diabetes-induced microvascular diseases, such as diabetic retinopathy and nephropathy [ 5 , 6 ]. Our previous work found that in a rat model of early diabetic nephropathy, islet transplantation could stop and reverse the progression of diabetic nephropathy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%